PENGARUH KINERJA KEUANGAN TERHADAP POTENSI KEBANGKRUTAN PADA PERUSAHAAN LQ 45 - Gabriellita; Richard F Simbolon (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
The objective of the research is to establish the impact of economic overall performance at the capability for financial ruin of LQ 45 corporations indexed at the Indonesia Stock Exchange in the period 2018-2020. This research makes use of secondary data obtained through the annual reports and financials of LQ 45 companies. The populace on this research is LQ 45 corporations indexed at the Indonesia Stock Exchange. The research sample was taken from 35 LQ 45 companies that survived the 2018-2020 period. This analysis was analysed mistreatment SPSS software package using the subsequent analysis: descriptive applied mathematics test, classical assumption test, multiple statistical regression test. The results of the study indicate that liquidity features a important result on the potential for bankruptcy with a sig. 0.000 < 0.05, gain has a significant effect on the potential for bankruptcy with a sig. 0.005 < 0.05, financial condition has a significant effect on the potential for bankruptcy with a sig value. 0.000 < 0.05, and activity has a significant effect on the potential for bankruptcy with a worth of sig. 0.000 < 0.05. at the same time all freelance variables have an effect on the potential for bankruptcy supported the F-count worth of 278574819.791 with a sig value. 0.000 < 0.05.